Polymeric Nanoparticles' Accumulation in Atopic Dermatitis: Clinical Comparison between Healthy, Non-Lesional, and Lesional Skin - Céline Try; Mona M. A. Abdel-Mottaleb; Arnaud Béduneau; Brice Moulari; Lionel Pazart; Chrystelle Vidal; Gaëlle Brunotte; Florence Castelain; Alf Lamprecht; Philippe Humbert; Yann Pellequer (MDPI AG, 2023)
A major limitation in the current topical treatment strategies for inflammatory skin disorders is the inability to selectively target the inflamed site with minimal exposure of healthy skin. Atopic dermatitis is one of the most prevalent types of dermatitis. The use of polymeric nanoparticles for targeting inflamed skin has been recently proposed, and therefore the aim of this proof-of-concept clinical study was to investigate the skin penetration and deposition of polymeric biodegradable nanoparticles in the atopic dermatitis lesions and compare the data obtained to the deposition of the particles into the healthy skin or lesion-free skin of the atopic dermatitis patients. For that, fluorescent PLGA nanoparticles in sizes of approximately 100 nm were prepared and applied to the skin of healthy volunteers and the lesional and non-lesional skin of atopic dermatitis patients. Skin biopsies were examined using confocal laser scanning microscopy to track the skin deposition and depth of penetration of the particles. Immunohistochemistry was performed to investigate the alteration in tight-junction protein distribution in the different types of skin. Results have shown that nanoparticles were found to have higher deposition into the atopic dermatitis lesions with minimal accumulation in healthy or non-lesional skin. This has been primarily correlated with the impaired barrier properties of atopic dermatitis lesions with the reduced production of Claudin-1. It was concluded that polymeric nanoparticles offer a potential tool for selective drug delivery to inflamed skin with minimal exposure risk to healthy skin.